Kaiser Sigismund Zur Herrschaftspraxis eines europäischen Monarchen (1368-1437) - Hruza, Karel (2012)
The present conference proceedings consist of 18 articles based on papers presented on 6th and 7th December 2007 at the international conference "Emperor Sigismund (†1437). Rulership in Practice, Charters and Rituals" at Masaryk-University's, Brno, Historical Institute. The conference's idea benefited from a twofold opportunity: To commemorate the anniversary of Sigismund's death on 9th December 1437 in the Moravian town of Znojmo and to conclude the international Vienna based Regesta-Imperii-project P 17519-G08 "Sigismund (†1437), Kaiser im Reich, in Ungarn und in Böhmen", which had been funded by the Austrian Science Fund (FWF) since 2004. Sigismund, the secondborn son of ever popular emperor Charles IV. (1316-1378), came to wear not only the crown of the Holy Roman Empire but also of the Hungarian and Bohemian Kingdoms. Thus he ruled over a truly European empire that embraced partly or in total modern day's Austria, Germany, Switzerland, Italy, France, Luxembourg, the Czech Republic, Hungary, Slovakia, Rumania, Bulgaria, Slovenia, Croatia, and Serbia. This vast geographical sphere of influence spanned very different cultural, social, economic and political realities, which make it difficult to grasp the integrity of Sigismund's complex reign, but make clear its extensive European dimensions. The current volume presents the mentioned project's first outcomes. The members of the Viennese team mainly concentrate on diplomatics and charter-issuing practice, subjects so far neglected in the scientific research dedicated to Sigismund and his time. Therefore their papers for the most part deal with diverse aspects of Sigismund's production of charters and letters. Including methodical approaches of neighbouring disciplines, they treat the question of typology of Sigismund's charters and charter-formulas as well as subjects of administrative and cultural history and communication studies. In addition the papers of the other involved international authors contribute to different aspects on the field of historical regional studies, administrative, religious, and cultural history as much as to the history of diplomacy, rituals, and art during the era of Sigismund's reign. Using instructive examples they all aim at shedding a light on the complex relations between Sigismund and his court to certain regions or social groups, or respectively on the role of written, oral, and symbolical communication and the use of ritual in practical rulership. The papers' main emphasis consists in Sigismund's relations to southwestern Germany, his rule in the Bohemian Lands and the historiographical work of Eberhard Windeck. The current volume throws a light on some aspects of Sigismund's rulership in practice, which either have not been dealt with at all by German historians so far, or at least seriously modify some of the popular ideas on Sigismund and his rule. The conference proceedings in their entirety give new impetus to scientific activity concentrating on the production of Sigismund's chancery and open new, innovative approaches to research on late medieval practice of royal rulership in general.